Streptococcus pyogenes streptolysin O as a cause of false-positive CAMP reactions. - Tapsall, J W (1984)
The synergistic hemolysis of sheep erythrocytes in the CAMP reaction by the sequential action of staphylococcal beta-lysin and the CAMP factor of group B streptococci is the only known function of this extracellular product of group B streptococci. The reaction forms the basis of the CAMP test used to identify group B streptococci because the CAMP factor is believed to be restricted to this group of organisms. However, on occasion other streptococci, notably group A streptococci, may produce a similar synergistic lysis of sheep erythrocytes. The nature of the synergistic lytic factor of group A streptococci responsible for this sequential hemolysis was investigated in a tube CAMP reaction system. The properties of this synergistic lytic factor were found to correspond to those of streptolysin O of group A streptococci. The synergistic lytic factor, like streptolysin O, was produced during the logarithmic phase of growth; the activity was increased by reducing agents and greatly decreased or abolished by heat, trypsin, cholesterol, and anti-streptolysin O, and it was immunogenic in rabbits. This would suggest that the synergistic hemolysis seen in the CAMP reaction system with group A streptococci is due to the action of those small amounts of streptolysin O which remain unoxidized and thus have a capacity to lyse the fragile beta-lysin-treated sheep erythrocytes.